HISTOPATHOLOGICAL DESCRIPTION OF THE LIVER OF WHITE RATS TREATED WITH YEAST - Hidayah, Ainul -; Suastika, Putu; Budiasa, Ketut; Samsuri, Samsuri; Berata, I Ketut; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2022)
This study aimed to determine the histopathological picture of the liver of white rats due to the treatment of yeast at several different doses. A total of 24 white rats were randomly divided into 4 treatment groups, namely P0: control; P1: giving yeast of 100 mg/kg BW; P2: 200 mg/kg BW; and P3: 300 mg/kg BW. The treatment dose was carried out for 21 days. On the 22nd day, all samples got euthanasia and a necropsy procedure was performed. The liver organs were taken to make histological preparations by staining with Hematoxylin Eosin. The variables observed included fatty degeneration and necrosis. The data obtained were analyzed using the Kruskal-Wallis test. The results showed that the administration of yeast at a dose of 100 mg/kg BW, 200 mg/kg BW, and 300 mg/kg BW was not significantly different (P>0.05) compared to the control (P0). It can be concluded that threating by yeast up to a dose of 300 mg/kg BW does not cause histopathological changes in the liver of white rats.